2003
DOI: 10.1063/1.1580646
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-contact organic field-effect transistors having low-dielectric layer under source and drain electrodes

Abstract: Articles you may be interested inSource/drain electrodes contact effect on the stability of bottom-contact pentacene field-effect transistors AIP Advances 2, 022113 (2012); 10.1063/1.4707164 Transparent organic field-effect transistors with polymeric source and drain electrodes fabricated by inkjet printing Appl. Phys. Lett. 92, 243307 (2008); 10.1063/1.2940232Polymer-based organic field-effect transistor using offset printed source/drain structures Appl.Influence of moisture on device characteristics of polyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 14 publications
0
34
0
Order By: Relevance
“…[23] In this study, bottom-contact TFTs were fabricated with a low-dielectric-constant polymer film (PMMA, 150 nm) between the Ta [26] Films 26±130 nm thick were fabricated by applying a constant anodization current (J~0.6 mA cm ±2 ) through the growing insulator, by ramping the voltage up to a limiting anodization voltage (V a = 20±100 V), which was maintained for several minutes until the current dropped. A 0.01 M citric acid aqueous solution was used as the electrolyte.…”
Section: Reviewmentioning
confidence: 99%
“…[23] In this study, bottom-contact TFTs were fabricated with a low-dielectric-constant polymer film (PMMA, 150 nm) between the Ta [26] Films 26±130 nm thick were fabricated by applying a constant anodization current (J~0.6 mA cm ±2 ) through the growing insulator, by ramping the voltage up to a limiting anodization voltage (V a = 20±100 V), which was maintained for several minutes until the current dropped. A 0.01 M citric acid aqueous solution was used as the electrolyte.…”
Section: Reviewmentioning
confidence: 99%
“…The low surface energy is similar to the surface modification effect exhibited by self-assembled monolayer (SAM) functionalizations and polymeric capping layer, such as hexamethyldisilazane (HMDS), [70] octadecyltrichlorosilane (OTS), [33,36,71] and other silanes, [71] or surface modification using spin-coated organic thin films, such as poly(a-methylstyrene) (PaMS), [72] poly(methyl methacrylate) (PMMA), [73] as well as poly(methyl silsesquioxane) (pMSSQ). [74] Linear alkyl and branched alkyl chains have been particularly effective to increase the mobility due to hydrophobicity [75] together with the type/orientation of the terminal groups on the SAM, [76,77] producing highly ordered films with improved film morphology, microstructures, and interface traps; despite the reports that modifiers such as OTS leads to improved mobilities despite smaller grain sizes.…”
Section: Resultsmentioning
confidence: 98%
“…Halik et al [1] demonstrated that large operating voltages were not an intrinsic feature of organic transistors, and the operating voltages and power dissipations of organic devices could be dramatically reduced by using extreme thin self-assembly film of silane-based molecular as dielectric. Apart from reducing the thickness of gate dielectric, many other methods [3][4][5][6][7][8][9][10][11][12][13][14] have been proposed to lower down the operating voltages and threshold voltages (V T ). The most attractive one among them is considered to be applying high-k material [2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from reducing the thickness of gate dielectric, many other methods [3][4][5][6][7][8][9][10][11][12][13][14] have been proposed to lower down the operating voltages and threshold voltages (V T ). The most attractive one among them is considered to be applying high-k material [2][3][4][5][6][7][8][9][10][11][12][13][14]. Until now, the reported high-k materials used in OFETs include HfO 2 [3], Al 2 O 3 [4], Barium Zirconate Titanate (BZT) [5], BZN (Bi 1.5 Zn 1.0 Nb 1.5 O 7 ) [6], SBT (SrBi 2 Ta 2 O 9 ) [7], Ta 2 O 5 [8], TiO 2 [9], and ZrO 2 [10,11].…”
Section: Introductionmentioning
confidence: 99%